1983
DOI: 10.1007/bf02554752
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal repair of rectocele

Abstract: A modification of Sullivan's procedure for endorectal repair of "low" rectocele was completed in 59 patients with local anesthesia. Associated anorectal pathology was corrected in all patients. The technique is described. At follow-up, the results were as follows: 37 excellent (62.7 per cent), 10 good (16.9 per cent), eight fair (13.6 per cent), and four poor (6.7 per cent).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 5 publications
0
39
0
3
Order By: Relevance
“…Many early studies failed to identify the symptoms the operation was aimed at addressing. Khubchandani et al 17 and Sehapayak 21 reported 63 and 49·5 per cent of patients respectively to be asymptomatic following transanal repair but did not state what symptoms the patients had originally. Block 2 observed no recurrence in 60 patients who underwent transanal repair, but commented that 77 per cent of the patients were asymptomatic before surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Many early studies failed to identify the symptoms the operation was aimed at addressing. Khubchandani et al 17 and Sehapayak 21 reported 63 and 49·5 per cent of patients respectively to be asymptomatic following transanal repair but did not state what symptoms the patients had originally. Block 2 observed no recurrence in 60 patients who underwent transanal repair, but commented that 77 per cent of the patients were asymptomatic before surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Anatomic and functional improvements with this technique have been described by many authors in both prospective and retrospective studies. [7][8][9][10][11][12][13][14][15][16][17][18] In the present study, we sought to demonstrate improvement in bowel function after transanal rectocele repair using a validated scoring system and to compare these postoperative results to those reported by a control group of asymptomatic patients. …”
mentioning
confidence: 99%
“…Das ausgeweitete Septum rectovaginale wird mit vier bis sechs Einzelknopfnähten quer gerafft, wobei der Musculus puborectalis mit gefasst und median vereinigt wird. Das Läppchen wird auf dem gerafften Perinealkörper fixiert, gekürzt und die Mukosa verschlossen [9].…”
Section: Der Transrektale Zugangunclassified
“…Hier sollten transrektale bzw. kombinierte Verfahren zur Anwendung kommen, ebenso bei anorektalen pathologischen Veränderungen und bei tiefer Rektozele [9]. Der pathophysiologische Ansatz geht auf Richardson [20] zurück.…”
Section: Fischer F Et Al Chirurgische Therapie Der Rektozeleunclassified